(untitled) (Polish Yearbook of International Law, 2024)
Russia’s aggression against Ukraine and the efforts to prosecute the perpetrators have renewed the debate regarding domestic and international criminal jurisdiction over the crime of aggression. Given the inter-state nature of this crime and its link to an act of aggression, the existence of which can be determined by the Security Council, the International Law Commission’s (ILC) relatively restrictive approach to the exercise of criminal jurisdiction prevailed, at least until 2022. Against this background, the discussion regarding the establishment of a Special Tribunal for the crime of aggression against Ukraine has significantly influenced the trajectory of the understanding of general international law concerning individual criminal responsibility for the crime of aggression. The interpretative paths adopted in the mid-1990s are gradually being abandoned. At the same time, an intense ongoing debate concerning the understanding of the phrase “international criminal courts, where they have jurisdiction” has not led to any conclusive arrangements. Still, what is known is that there is a certain group of states for which such courts can be created through bilateral agreement between the state concerned and the United Nations, on the recommendation of the UN General Assembly.